A Synchronization Model of Distributive Justice in Motor Vehicle Tax Regulation - Yuni Puspitasari; Nadir Nadir; Win Yuli Wardani (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Motor Vehicle Tax (Pajak Kendaraan Bermotor/PKB) is a major source of regional revenue in Indonesia. However, the current administrative mechanism for determining the Motor Vehicle Sales Value (Nilai Jual Kendaraan Bermotor/NJKB) fails to adequately reflect the economic depreciation of vehicles, creating potential distributive injustice in tax assessment. This study examines the synchronization of PKB regulations, identifies inconsistencies between the administratively determined NJKB and actual market value, and develops a regulatory reconstruction model based on Hans Kelsen’s theory of the hierarchy of legal norms and John Rawls’s theory of distributive justice. Using a normative legal methodology with statutory, conceptual, and comparative approaches, the study finds that substantive regulatory inconsistencies remain despite formal legal synchronization. It proposes a Distributive Justice-Based Synchronization Model that strengthens statutory norms, adopts market-responsive depreciation, harmonizes implementing regulations, and promotes a fairer, more legally certain regional tax system.